Agricultural enterprises in the German Commercial Code - Gyuris, Árpád (Studia Mundi – Economica, 2021)
The paper intends to present how the German Commercial Code (Handelsgesetzbuch, HGB) defines the concept of merchant (Kaufmann), which crucially determines the applicability of German laws related to commerce. Merchants can both be natural or legal persons according to German law. In 1900, when the HGB stept in force, agrarian companies were not granted the opportunity to registrate themselves as merchants. This approach changed in 1976, when agrobusinesses were offered the opportunity to be considered mechants, which had particular significance in the case of new agrarian companies run on the basis of modern principles. The most significant difference in the current regulation between different types of businesses and persons is that those carrying out commercial activities in the strong sense count as merchants even without registration (if the aim of the business requires this), whereas agrobusinesses do not, they only acquire this status after registration.